Influence of the aftereffect of mineral fertilizers applied at different rates and ratios on the fields of winter wheat on the structure of the millet crop - SH.I.Irnazarov; A.T.Bekmurodova; D.O.Baxtiyorova (Zien Journals, 2022)
The article presents the aftereffect of the norms and ratios of mineral fertilizers used in the cultivation of winter wheat on the structure of the yield of millet grown as a re-crop in the stubble. As a result of an increase in the norms and ratio of mineral fertilizers and an increase in the number of residues in the soil, an increase in the productive millet eating from 0.4 to 0.9 pieces was noted, and an increase in the length of the panicle from 1 cm to 3 cm, the number of grains in the panicle increased from 20 to 99 grains, The grain mass of the panicle increased from 5.2 to 6.3 g, the mass of the grain of the panicle increased from 0.7 g to 1.8 g, the mass of 1000 grains increased compared to the control variant by 0.5 g - 1.8 g. , the nature of millet grain increased from 2 g/l to 11 g/l compared with the control variant.
Keywords: millet; stubble; potassium; phosphorus